PENGARUH PERSONAL BRANDING VANESSA AXELIA MELALUI TAYANGAN â€œTHE VOICEâ€ RCTI TERHADAP SIKAP IMITASI REMAJA DI SURABAYA - Ocvitalia, Shally; Hamim, Hamim; Soenarjanto, Bagus (Universitas 17 Agustus 1945 Surabaya, 2018)
The Voice Indonesia is one in the million of reality show programs in RCTI. Thisprogram succesed catching attention of many people and get a high rating in everyepisode. And, there is a participants who can catch so many attention from viewers, she isnamed Vanessa Axelia, she is 19 years old and came from Surabaya Started from thiscase, finally makes me as a researcher want to know the influence of personal brandingby Vanessa Axelia through The Voice RCTI episodes to tenenagerâ€™s imitation inSurabaya. This descriptive research is using a quantitative method. The evaluation fromthis research is personal branding of 66,8% influence on teenagerâ€™s imitation attitude inSurabaya. Like a personal branding theory by Peter Montoya who said there are 3 mostimportant things to building personal branding. There are competency, style andstandard. From that elements will correlated with imitation theory from Bandura whichare attention, retention, reproduction and motivation.Keywords : personal branding, imitation attitude of teenagers, The Voice RCTI